Gender Roles and the Gender Expectations Gap - Francesco D'Acunto; Ulrike Malmendier; Michael Weber (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
Expectations about economic variables vary systematically across genders. In the domain of inflation, women have persistently higher expectations than men. We argue that traditional gender roles are a significant factor in generating this gender expectations gap as they expose women and men to different economic signals in their daily lives. Using unique data on the participation of men and women in household grocery chores, their resulting exposure to price signals, and their inflation expectations, we document a tight link between the gender expectations gap and the distribution of grocery shopping duties. Because grocery prices are highly volatile, and consumers focus disproportionally on positive price changes, frequent exposure to grocery prices increases perceptions of current inflation and expectations of future inflation. The gender expectations gap is largest in households whose female heads are solely responsible for grocery shopping, whereas no gap arises in households that split grocery chores equally between men and women. Our results indicate that gender differences in inflation expectations arise due to social conditioning rather than through differences in innate abilities, skills, or preferences.
urn:nbn:de:hebis:30:3-616567
Keywords: C90; D14; D84; E31; E52; G11; 330; Gender Gap; Expectations; Perceptions; Experiences; Social Conditioning